Development of a PC based smart card reader - 453179 Manobindra Gandhi Thangarajoo (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2002